Making Mudarabah workable: altering risk-return profiles through equity Kickers - Mustaffa Kamil, Nazrol Kamil; Bacha, Obiyathulla Ismath (2011)
Critics of contemporary Islamic finance often highlight the absence of meaningful presence of equity-based financing instruments such as mudarabah. It has been argued that this is attributable to inter alia, the agency problems inherent in mudarabah financing. Within a risk and return framework, mudarabah financing presents an uninviting commercial proposition to financiers. The use of equity kickers effectively shifts the risk/return balance in favour of the rabbal mal and thereby possibly rekindling interest in mudarabah on the part of financiers. This paper explores the dynamics of such an employment of equity kickers. Our analysis shows that equity kickers are particularly expedient, from the financier’s perspective, when project durations are short, expected profitability is less assuring and when mudarib’s equity stake is high. In addition, it is demonstrated that the profit sharing ratio can be used as a balancing mechanism to achieve equitability between the interests of the rabbal mal and mudarib.